Moroccan entomopathogenic nematodes as potential biocontrol agents against Dactylopius opuntiae (Hemiptera: Dactylopiidae) - El Aalaoui, Mohamed; Mokrini, Fouad; Dababat, Abdelfattah A.; Lahlali, Rachid; Sbaghi, Mohamed (Springer, 2022)
Dactylopius opuntiae (Cockerell) (Hemiptera: Dactylopiidae) or prickly pear cochineal, is the most damaging pest on cactus species with heavy economic losses worldwide. The efficacy of two Moroccan EPN isolates; Steinernema feltiae (Filipjev) (Rhabditida: Steinernematidae) and Heterorhabditis bacteriophora (Poinar) (Rhabditida: Heterorhabditidae) (applied at 25, 50, and 75 IJs cm−2) against D. opuntiae nymphs and young females were evaluated under both laboratory bioassays and field conditions. Results showed that S. feltiae was more effective, causing higher mortality of nymphs and adult females (98.8% and 97.5%, respectively) after 8 days of exposure, resulting in an LT50 value of 5.9 days (nymph) and 6.0 days (young female). While, H. bacteriophora had lower mortalities (83.8% for nymph and 81.3% for adult females). For the cochineal nymphs and adult females, no significant difference was observed among S. feltiae at 25, 50, and 75 IJs cm−2, and the positive control, D-limonene applied at 0.5 g/L which was used due to its high effectiveness against nymphs and females of D. opuntiae. In the field experiment, D-limonene at 0.5 g/L and S. feltiae applied at 75 IJs cm−2 were effective in reducing nymph and adult female populations by 85.3–93.9% at 12 days of post exposure period. To our knowledge, this work is the first report on the use of EPNs to control D. opuntiae. Thus, in addition to D-limonene, both Moroccan EPN isolates S. feltiae, and H. bacteriophora could be used as part of the integrated pest management strategy against D. opuntiae. Many factors such as temperature can affect the establishment and effectiveness of EPNs under field conditions. Therefore, additional studies under field conditions are needed.